2010
DOI: 10.1177/1477370809347942
|View full text |Cite
|
Sign up to set email alerts
|

Protection and Assistance to Victims of Human Trafficking in Serbia: Recent Developments

Abstract: The paper reviews recent developments in the system of protection, assistance and support of victims of human trafficking in Serbia. The establishment of the Agency for Co-ordination of Protection of Victims of Trafficking in Human Beings in 2003, the issuing of the Instruction on Conditions for Obtaining Temporary Residence Permit for Foreign Citizens — Victims of Trafficking in Human Beings by the Minister of Interior in 2004, and the adoption of the Strategy to Combat Trafficking in Human Beings in the Repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 5 publications
(7 reference statements)
0
25
0
Order By: Relevance
“…Consistently throughout the literature, legal aid is highly recommended as a necessary service for CSTVs (Blue BlindFold, 2012;ILO, 2006;Kaufman & Crawford, 2011;Macy & Johns, 2011;Rigby et al, 2012;Simeunovic-Patic & Copic, 2010;UNODC, 2007;Van der Keur, 2013;Wölte & Tautz, 2007). Macy and Johns (2011) advise that legal representation for the CSTV should be provided as soon after the discovery of the CSTV as possible.…”
Section: Recoverymentioning
confidence: 94%
See 2 more Smart Citations
“…Consistently throughout the literature, legal aid is highly recommended as a necessary service for CSTVs (Blue BlindFold, 2012;ILO, 2006;Kaufman & Crawford, 2011;Macy & Johns, 2011;Rigby et al, 2012;Simeunovic-Patic & Copic, 2010;UNODC, 2007;Van der Keur, 2013;Wölte & Tautz, 2007). Macy and Johns (2011) advise that legal representation for the CSTV should be provided as soon after the discovery of the CSTV as possible.…”
Section: Recoverymentioning
confidence: 94%
“…Guiding principles Rights-based care Asquith & Turner, 2008;Blue BlindFold, 2012;Frederick, 2005;ILO, 2006;IOM, 2004;Kaufman & Crawford, 2011;Macy & Johns, 2011;Rigby et al, 2012;SARI, n.d.;SimeunovicPatic & Copic, 2010;Thompson, G. n.d.;UNODC, 2007;Wirsing, 2012;Wö lte & Tautz, 2007 Trauma-informed care Asquith & Turner, 2008;Blue BlindFold, 2012;Frederick, 2005;ILO, 2006;IOM, 2004;Macy & Johns, 2011;Rigby et al, 2012;SARI, n.d.;Simeunovic-Patic & Copic, 2010;Thompson, G. n.d.;UNODC, 2007;Van der Keur, 2013;Wirsing, 2012 professionals to be trained on CSEC and its effects, and they should be gender appropriate and able to maintain confidentiality (ILO, 2006;SARI, n.d.). The literature stressed that CSTVs should not be forced to test for diseases including STIs and HIV/AIDS (Frederick, 2005;ILO, 2006;Macy & Johns, 2011).…”
Section: Services Publication Authorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Upon their release from captivity, many women are found to be in the violation of immigration laws and returned to their home countries (Waugh 2006;Bernat and Zhilina 2010). Some nations like the United States, Italy, and the United Kingdom have provisions for a grace period during which victims are allowed to stay in the country under specific conditions, commonly requiring their cooperation with the law enforcement (Waugh 2006;Simeunovic-Patic 2010). Even in the rare cases when former victims agree to help prosecutors and testify in court against traffickers, they have few resources and little protection against retaliation (Waugh 2006).…”
Section: Victims' Response To Traffickingmentioning
confidence: 99%
“…Different levels of compliance with the UN Anti-Trafficking Protocol have attracted scholars' attention [8,9,15,16,[26][27][28][29][30]. This research has identified a set of factors that drive states' efforts to prosecute and prevent human trafficking as well as to protect its victims.…”
Section: Explaining Anti-trafficking Effortsmentioning
confidence: 99%